Pelatihan Pembinaan Kebugaran Jasmani Peserta Ekstrakurikuler Olahraga SMA 3 Sentani, Kabupaten Jayapura - Daniel Womsiwor; Ansar CS; Dewi Nurhidayah; Baharuddin Hasan; Nasruddin Nasruddin; Muh Syaiful Syam (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
This community service activity aims to increase the knowledge of students participating in sports extracurriculars about developing physical fitness, regarding forms of physical fitness tests, and compiling menus for coaching physical fitness training. This activity was carried out at SMA Negeri 3 Sentani as an activity partner. The results of this activity show that: 1) sports extracurricular participants understand various aspects of physical fitness, 2) sports extracurricular participants are able to take a physical fitness test, and 3) sports extracurricular participants can design a physical fitness training menu. The monitoring and evaluation process is carried out through a pretest and posttest to measure students' knowledge of aspects of physical fitness, fitness tests, and exercise menus before and after activities are carried out. Based on the results of the pre-test and post-test, the average pre-test score was 7.5 and the post-test was 13.4. These results indicate an increase in student knowledge after participating in physical fitness development training in sports extracurriculars at SMA Negeri 3 Sentani.